Rancang Bangun Sistem Exhaust Fan Otomatis Berbasis Sensor DHT11 dan Mikrokontroler ESP32 untuk Peningkatan Kualitas Udara di Smoking Area - Rifky Irfani; Achmad Aziz Rahmanto; Muhammad Edgar Gazazanata (Jurnal Engine: Energi, Manufaktur, dan Material, 2025)
Air pollution in smoking areas can significantly impact human health and reduce indoor air quality. Poor ventilation systems often fail to respond to real-time environmental changes, leading to increased exposure to harmful particles. This research develops an automatic exhaust fan system utilizing a DHT11 sensor and an ESP32 microcontroller to optimize air circulation. The system activates when the temperature exceeds 27°C or humidity surpasses 60%, ensuring effective ventilation control. The study employs a prototyping approach consisting of system design, hardware and software implementation, and performance testing. Results indicate a 20% reduction in energy consumption compared to manual operation, highlighting the system's efficiency. The DHT11 sensor records a temperature deviation of ±0.5°C and a humidity accuracy of ±2%, confirming its reliability. This system not only improves air quality but also supports energy efficiency, making it a viable solution for enclosed smoking areas in public spaces.